A Reduction of Derivational and Inflectional Morphemes - abasali vafaei (Matn/Pizhūhī-i Adabī, 2009)
Language, like other natural and social phenomena, is constantly changing. From different linguistic perspectives, it has undergone a lot of changes. One of the linguistic debates has been in the domain of lexical and phonetic changes. It sometimes brings about semantic and categorical changes and at times, we can notice a change in conversions, reductions, and other types of changes. This study is an attempt to examine the reduction of derivational and inflectional morphemes of the Persian language and to analyze the role of the morphemes’ relaxation in the reduction of consonants, vowels, and syllables. Moreover, it regulates such reductions according to the type of linguistic categories. This novel issue has not been significantly researched, nor has it been discussed in grammar books.